IMPLEMENTASI BIMBINGAN KONSELING SPIRITUAL PASIEN REHABILITASI NAPZA DI RUMAH SAKIT JIWA PROF. DR. M.ILDREM MEDAN - Halasan Leonardus Simamora; Erita Gustina; Huwaina Af’idah (SINERGI : Jurnal Riset Ilmiah, 2026)
The abuse of narcotics, psychotropic substances, and addictive substances (NAPZA) is a serious social and health problem in Indonesia. Many victims of drug abuse experience psychological disorders such as anxiety, depression, and loss of motivation to live. In the context of rehabilitation, spiritual counseling is an effective approach to assist patients in their recovery process, both psychologically and spiritually. This study aims to implement spiritual counseling for drug rehabilitation patients at Prof. Dr. M. Ildrem Mental Hospital, Medan. The method used was a case study with a qualitative approach with two drug rehabilitation patients. The counseling process was conducted through a spiritual approach that included strengthening faith, practicing religious practices, and providing emotional support based on religious values. The study results showed positive changes in patients' behavior, mindset, and coping mechanisms after receiving spiritual counseling intervention. This study concludes that the implementation of spiritual counseling can facilitate the recovery process and improve the overall quality of life of drug rehabilitation patients.